Nas trilhas do impulso vital: compreendendo a mística bergsoniana - Medeiros, Azize Maria Yared de (2014)
The object of this essay is to understand the mystic formulated by Henri Bergson, in his last work The Two Sources of Morality and Religion. The philosopher s reflections show two kinds of religious manifestations, which he called static and dynamic. The first one is characterized by institutionalized religions, with its dogmas and doctrines, whose traces are recognized as responsible for the processes of social cohesion. The second, known as dynamic, is related with the mystic, object of analysis of this essay. The multiple meanings of the term mystic and the complexity of the phenomenon required research about the historic and linguistic development of its roots. Mystic is understood in this thesis as a subjective human experience, which establishes, in a conscious way, a direct relationship, with no intermediary, with God, or the Absolute or even better, with Mystery, causing deep transformation in the subject of the experience, with social and communal consequences. Mystic, a definitive expression of bergsonian metaphysics, derives from an intuitive process and establishes the impossibility of intelligence and rationality to reach the Absolut. His reflections are based on theories of evolution. He argues that there is no opposition between creationism and evolution, and establishes the existence of élan vital, a vital force which, along with matter, develops the planet and its species. We found, in the makeup of Bergson s metaphysic thoughts and using his intuitive method, elements which can sustain the proposal thesis: we understand that the individual impetus for the search of meaning is part of the structure of human consciousness, and the comprehension that there is an ascendant evolutionary process, inherent to life and undertaken by humanity, reaches its summit and the core, not only in the mystic experience, but also in the loving action generated by it.